Sodium-ion battery positive electrode material and preparation method thereof, sodium-ion battery and electric equipment
By using a combination material of a P2 phase cladding layer and an O3 phase layered oxide matrix in the positive electrode material of the sodium ion battery, the problems of insufficient structural stability of the positive electrode material and high surface residual alkali in the prior art are solved, and the high cycle performance and capacity-taking effect of the battery are achieved.
Patent Information
- Application Number
- CN202411963034.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The structural stability of the existing sodium ion battery positive electrode materials is insufficient and susceptible to hydrofluoric acid, resulting in poor circulation performance and high residual alkali on the surface, affecting the overall performance of the battery.
The sodium ion battery positive electrode material including the NaxMn1-yM'yOzFβ coating layer of P2 phase is used to combine it into a combination material of the P2 phase coating layer and the O3 phase layered oxide matrix by first sintering to improve structural stability and reduce surface residual alkali.
It significantly improves the circulation performance of sodium ion batteries, allowing the battery to take into account both capacity and circulation performance, while reducing hydrogen fluoride erosion and ginger Taylor effect, and improving the stability of the battery.
Smart Images

Figure CN119905554A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and particularly to a cathode material for a sodium-ion battery, a preparation method thereof, a sodium-ion battery, and an electricity-related device. Background Art
[0002] In recent years, sodium-ion batteries have shown excellent development and application prospects in the fields of consumer electronics, electric vehicles, and large-scale energy storage. Due to the advantages of high capacity, simple preparation, and adjustable voltage range of sodium-layered oxides, they have received extensive attention and research in the academic and industrial fields. Coating modification is widely used and effective in the cathode materials of sodium-layered oxides. Currently, oxides are usually used for coating, such as Fe2O3, NiO, Al2O3, etc., but the oxide coatings are easily eroded by hydrofluoric acid, affecting the coating modification effect. Summary of the Invention
[0003] The purpose of the present invention is to provide a cathode material for a sodium-ion battery, a preparation method thereof, a sodium-ion battery, and an electricity-related device, so as to improve the structural stability of the cathode material for a sodium-ion battery, reduce the surface residual alkali, and further improve the cycle performance of the battery, making the battery take into account both capacity and cycle performance.
[0004] To achieve the above purpose, in the first aspect of the present invention, a cathode material for a sodium-ion battery is provided. The cathode material includes a matrix and a coating layer coated on the surface of the matrix. The matrix includes layered oxides; the coating layer includes Na x Mn 1-y M' y O z F β , where 0.6 < x < 0.8, 0 < y ≤ 0.05, 1.9 < z ≤ 2.1, 0 < β ≤ 0.05, and M' is selected from at least one of Ni, Fe, Co, Ti, Li, and Mn.
[0005] In some embodiments, the matrix includes layered oxides with an O3 phase; optionally, the chemical general formula of the layered oxides is Na i MF α O j , where 0.6 < i < 1.1, 0 ≤ α ≤ 0.05, 1.9 < j ≤ 2.1, and M is selected from at least one of Ni, Fe, Mn, Co, Ti, Cu, Ca, Zn, Mg, Al, Y, Ce, Sr, Sn, Ba, La, and Li.
[0006] In some embodiments, the mass ratio of the P2 phase to the O3 phase is (0.01 - 0.05):1.
[0007] In some embodiments, the cathode material satisfies at least one of the following conditions:
[0008] a. The concentration of fluorine element contained in the matrix is less than the concentration of fluorine element contained in the coating layer;
[0009] b. The chemical general formula of the coating layer is Na x Mn 1-y M' y O z F β , where 0.6 < x < 0.7, 0 < y ≤ 0.02, 1.9 < z ≤ 2.1, 0 < β ≤ 0.02, and M' is selected from at least one of Mn, Co, and Li;
[0010] c. The average thickness of the coating layer is 5 - 50 nm;
[0011] d. The D50 of the cathode material is 3 - 20 μm;
[0012] e. The mass of the coating layer accounts for 1 - 5% of the mass of the matrix.
[0013] The second aspect of the present invention provides a method for preparing a cathode material for a sodium-ion battery as described in the first aspect, the method comprising:
[0014] Performing a first sintering on a first mixture including a manganese-containing compound, a fluoride containing M', and the matrix to obtain the cathode material.
[0015] In some embodiments, the method satisfies at least one of the following conditions:
[0016] (1) The manganese-containing compound is selected from at least one of MnCO3, MnO, Mn2O3, MnO2, Mn2O7, and Mn3O4;
[0017] (2) The M' in the fluoride containing M' is selected from at least one of Ni, Fe, Co, Ti, Li, and Mn;
[0018] (3) The temperature of the first sintering is 400 - 700 °C, and the time is 4 - 8 h; optionally, the temperature of the first sintering is 500 - 600 °C, and the time is 6 - 8 h;
[0019] (4) The heating rate of the first sintering is 1 - 5 °C / min; optionally, the heating rate of the first sintering is 1 - 3 °C / min;
[0020] (5) The matrix is polycrystalline particles or single-crystalline particles;
[0021] (6) The mass ratio of the coating layer to the matrix in the first mixture is (0.01 - 0.05):1.
[0022] In some embodiments, the matrix is obtained by performing a second sintering on a second mixture including a sodium source and a metal M source.
[0023] In some embodiments, the method satisfies at least one of the following conditions:
[0024] A. the sodium source is selected from at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate;
[0025] B. the metal M source is selected from at least one of an oxide containing metal M, a hydroxide containing metal M, and a carbonate containing metal M;
[0026] C. M in the metal M source is selected from at least one of Ni, Fe, Mn, Co, Ti, Cu, Ca, Zn, Mg, Al, Y, Ce, Sr, Sn, Ba, La, and Li;
[0027] D. The second sintering temperature is 800-1100°C and the time is 10-15h;
[0028] E. The heating rate of the second sintering is 1-3°C / min;
[0029] F. The element molar ratio of sodium to metal M in the second mixture is (0.6-1.1):1.
[0030] A third aspect of the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material according to the first aspect.
[0031] The fourth aspect of the present invention provides an electrical device, comprising the sodium ion battery described in the third aspect.
[0032] Compared with the prior art, the technical solution provided by the present invention has at least the following advantages:
[0033] The sodium ion battery positive electrode material provided by the present invention has a P2 phase coating layer with good structural stability. The formed F-Mn bond can not only reduce the dissolution of manganese caused by hydrogen fluoride corrosion in the electrolyte, but also inhibit the Mn 3+ The lattice distortion caused by the Jan-Taylor effect can significantly improve the cycle performance of the battery. On the other hand, the coating layer can reduce the residual sodium on the surface of the matrix, and can also provide charge compensation and fast Na+ during the sodium ion extraction / embedding process. + Diffusion channel, and alleviate the trend of voltage drop during discharge, so that the battery can take into account both capacity and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1It is a comparison chart of the discharge specific capacity of batteries assembled with the positive electrode materials obtained in Example 1, Comparative Example 1, and Comparative Example 3 provided by the exemplary embodiment of the present invention within a voltage range of 2.0-4.3V at rates of 0.1C, 0.2C, and 1C;
[0035] Figure 2 This is a comparison chart of the discharge medium voltage of batteries assembled with the positive electrode materials obtained in Example 1 and Comparative Example 4 provided by the exemplary embodiment of the present invention within a voltage range of 2.0-4.3V at rates of 0.1C, 0.2C, and 1C;
[0036] Figure 3 is a SEM image of the positive electrode material obtained in Example 1 provided by the present invention;
[0037] Figure 4 is the XRD spectrum of the positive electrode material obtained in Example 1 provided by the present invention;
[0038] Figure 5 is the XRD spectrum of the fluorine-doped sodium manganate obtained from the control group provided by the present invention;
[0039] Figure 6 is a cross-sectional EPMA image of the positive electrode material obtained in Example 1 provided by the present invention;
[0040] Figure 7 This is a cross-sectional electron microscope image of the positive electrode material obtained in Example 1 provided by the present invention;
[0041] Figure 8 This is a diagram of selected fluorine element analysis points of a cross-sectional EDS of a positive electrode material obtained in Example 1 provided as an exemplary embodiment of the present invention. DETAILED DESCRIPTION
[0042] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0043] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0044] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0045] As described above, the first aspect of the present invention provides a cathode material for a sodium-ion battery. The cathode material includes a matrix and a coating layer coated on the surface of the matrix. The matrix includes a layered oxide; the coating layer includes Na x Mn 1-y M' y O z F β , where 0.6 < x < 0.8, 0 < y ≤ 0.05, 1.9 < z ≤ 2.1, 0 < β ≤ 0.05, and M' is selected from at least one of Ni, Fe, Co, Ti, Li, and Mn.
[0046] For the cathode material for a sodium-ion battery provided by the present invention, on the one hand, the P2-phase coating layer has good structural stability. The formed F-Mn bond can not only reduce the dissolution of manganese elements caused by the erosion of hydrogen fluoride in the electrolyte, but also inhibit the lattice distortion caused by the Jahn-Teller effect of Mn 3+ , which can significantly improve the cycle performance of the battery. On the other hand, the coating layer can reduce the residual sodium on the surface of the matrix, and can also provide charge compensation, provide a fast Na + diffusion channel, and relieve the downward trend of the discharge mid-voltage during the sodium ion extraction / insertion process, so that the battery takes into account both capacity and cycle performance.
[0047] In some embodiments, the matrix includes a layered oxide with an O3 phase; optionally, the chemical general formula of the layered oxide is Na i MF α O j , where 0.6 < i < 1.1, 0 ≤ α ≤ 0.05, 1.9 < j ≤ 2.1, and M is selected from at least one of Ni, Fe, Mn, Co, Ti, Cu, Ca, Zn, Mg, Al, Y, Ce, Sr, Sn, Ba, La, and Li; the O3-phase matrix can provide sufficient initial Na + reserves to achieve a higher charge-discharge specific capacity; in addition, when the matrix contains a small amount of fluorine element, it can not only avoid capacity reduction, but also improve the cycle stability at high voltages.
[0048] In some embodiments, the mass ratio of the P2 phase to the O3 phase is (0.01 - 0.05):1. For example, it can be 0.010, 0.015, 0.020, 0.025, 0.030, 0.035, 0.040, 0.045, 0.050 or any value between (0.01 - 0.05):1; the sodium-ion battery cathode material obtained in this embodiment has more excellent electrochemical performance. Through creative research, the present invention has found that when the proportion of the P2 phase is within the foregoing range, it is more conducive to effectively blocking the damage of the electrolyte to the material structure, and it will not cause an increase in impedance and a deterioration in rate performance due to a relatively high proportion of the P2 phase. Therefore, the present invention preferably limits the mass ratio of the P2 phase to the O3 phase to (0.01 - 0.05):1.
[0049] In some embodiments, the cathode material satisfies at least one of the following conditions:
[0050] a. The concentration of fluorine element contained in the matrix is less than the concentration of fluorine element contained in the coating layer; a large amount of fluorine element doping in the coating layer can inhibit the oxygen loss caused by the high-voltage O 2- / O - redox reaction, alleviate the downward trend of the discharge medium voltage, and at the same time, a small amount of fluorine element doping in the matrix core avoids capacity reduction.
[0051] b. The chemical general formula of the coating layer is Na x Mn 1-y M' y O z F β , where 0.6 < x < 0.7, 0 < y ≤ 0.02, 1.9 < z ≤ 2.1, 0 < β ≤ 0.02, and M' is selected from at least one of Mn, Co, and Li; in this embodiment, the sodium-ion battery cathode material obtained by the present invention has more excellent electrochemical performance.
[0052] c. The average thickness of the coating layer is 5 - 50 nm; for example, it can be 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm or any value between 5 - 50 nm. When the average thickness of the coating layer is within a suitable range, it can not only improve the coating uniformity, thereby enhancing the isolation effect between the matrix and the electrolyte, but also ensure the capacity of the cathode material.
[0053] d. The D50 of the cathode material is 3 - 20 μm; for example, it can be 3 μm, 4 μm, 5 μm, 8 μm, 10 μm, 15 μm, 18 μm, 20 μm or any value between 3 - 20 μm;
[0054] e. The mass of the coating layer accounts for 1 - 5% of the mass of the matrix; for example, it can be 1%, 2%, 3%, 4%, 5% or any value between 1 - 5%.
[0055] It should be noted that, in the present invention, the fluorine concentration in the matrix and the fluorine concentration in the coating layer refers to the relative content of the fluorine element in the matrix, and the fluorine concentration in the coating layer refers to the relative content of the fluorine element in the coating layer, which can be measured by EDS point scanning and EPMA detection methods.
[0056] D50 in the present invention refers to the particle size corresponding to when the cumulative particle size distribution percentage of the particles reaches 50%.
[0057] As mentioned above, the second aspect of the present invention provides a method for preparing the positive electrode material for a sodium ion battery as described in the first aspect, the method comprising:
[0058] The positive electrode material is obtained by first sintering a first mixture including a manganese-containing compound, a fluoride containing M' and the matrix.
[0059] In some embodiments, the first sintering is performed in an oxygen-containing atmosphere; optionally, the oxygen-containing atmosphere is air or oxygen.
[0060] In some embodiments, the method satisfies at least one of the following conditions:
[0061] (1) The manganese-containing compound is selected from at least one of MnCO3, MnO, Mn2O3, MnO2, Mn2O7, and Mn3O4;
[0062] (2) the M' in the M'-containing fluoride is selected from at least one of Ni, Fe, Co, Ti, Li, and Mn;
[0063] (3) The first sintering temperature is 400-700° C., and the time is 4-8 hours; optionally, the first sintering temperature is 500-600° C., and the time is 6-8 hours;
[0064] (4) The heating rate of the first sintering is 1-5°C / min; optionally, the heating rate of the first sintering is 1-3°C / min;
[0065] (5) The matrix is a polycrystalline particle or a single crystal particle;
[0066] (6) The mass ratio of the coating layer to the substrate in the first mixture is (0.01-0.05):1.
[0067] It should be noted that in the present invention, the matrix is a polycrystalline particle, which means a secondary sphere composed of primary particles with a significant crystal interface, and the matrix is a single crystal particle, which means a plate-like grain without a significant crystal interface, which can be measured by SEM.
[0068] In some embodiments, the matrix is obtained by performing a second sintering on a second mixture including a sodium source and a metal M source.
[0069] In some embodiments, the second sintering is performed in an oxygen-containing atmosphere; optionally, the oxygen-containing atmosphere is air or oxygen.
[0070] In some optional implementations of the present application, the method satisfies at least one of the following conditions:
[0071] A. the sodium source is selected from at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate;
[0072] B. the metal M source is selected from at least one of an oxide containing metal M, a hydroxide containing metal M, and a carbonate containing metal M;
[0073] C. M in the metal M source is selected from at least one of Ni, Fe, Mn, Co, Ti, Cu, Ca, Zn, Mg, Al, Y, Ce, Sr, Sn, Ba, La, and Li;
[0074] D. The second sintering temperature is 800-1100°C and the time is 10-15h;
[0075] E. The heating rate of the second sintering is 1-3°C / min;
[0076] F. The element molar ratio of sodium to metal M in the second mixture is (0.6-1.1):1.
[0077] In the present invention, there is no particular limitation on the preparation method of the oxide containing metal M, the hydroxide containing metal M, and the carbonate containing metal M. Those skilled in the art can select them according to technical means known in the art, and the present invention will not go into details here. The present invention will exemplarily provide some specific preparation methods in the examples below.
[0078] The method is to obtain the Na2 phase by first sintering the matrix with the manganese compound and the fluoride of M'. y MnM' z O 2-β F β The sodium ion battery positive electrode material is coated with an O3 phase layered oxide. The in-situ coating process is simple to operate, easy to control, has a short process flow, and less environmental pollution. The prepared coating layer is evenly distributed and has complete coverage.
[0079] As mentioned above, the third aspect of the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in the first aspect above.
[0080] As mentioned above, the fourth aspect of the present invention provides an electrical device, including the sodium ion battery described in the third aspect.
[0081] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.
[0082] Example 1
[0083] This embodiment prepares a sodium ion battery positive electrode material, and the preparation steps are as follows:
[0084] (1) Preparation of precursor (metal M-containing hydroxide): nickel sulfate, manganese sulfate, titanium sulfate and magnesium sulfate were dissolved in 1000 mL of water at a molar ratio of Ni:Mn:Ti:Mg of 0.40:0.52:0.05:0.03 to obtain a mixed solution with a metal ion concentration of 1 mol / L, and then 50 mL of 20 wt% ammonia water and 80 mL of 38 wt% sodium hydroxide solution were added to perform precipitation reaction. After solid-liquid separation of the obtained reaction product, the solid product was washed and dried in turn to obtain a precursor Ni with a D50 of 3.5 μm. 0.40 Mn 0.52 Ti 0.05 Mg 0.03 (OH)2; the conditions of the precipitation reaction are: temperature 70°C, time 50h;
[0085] (2) Matrix preparation: In the presence of air, the precursor obtained in step (1) was mixed with Na2CO3 at a molar ratio of n(Na) / n(M) of 1.03, and then subjected to a second sintering to obtain a matrix Na2CO3 of O3 phase. 0.86 Ni 0.40 Mn 0.52 Ti 0.05 Mg 0.03 O2; the second sintering conditions are: heating rate of 1 ° C / min, temperature of 980 ° C, time of 15h;
[0086] (3) Preparation of positive electrode material for sodium ion battery: In the presence of air atmosphere, 100 g of the substrate obtained in step (2), 0.8 g of manganese tetraoxide, and 0.2 g of manganese fluoride were mixed and sintered for the first time to obtain a positive electrode material S1 for a sodium ion battery; the conditions of the first sintering were: temperature of 550° C., time of 6 h, and heating rate of 2° C. / min.
[0087] Example 2
[0088] In this embodiment, a sodium ion battery positive electrode material is prepared. The preparation method is basically the same as the preparation method in Example 1, except that in step (3) of this embodiment, the amount of manganese tetraoxide is 3.2 g, and the amount of manganese fluoride is 0.8 g.
[0089] The sodium ion battery positive electrode material S2 is prepared.
[0090] Example 3
[0091] This embodiment prepares a sodium ion battery positive electrode material, and its preparation method is basically the same as the preparation method of Example 1, except that in step (3) of this embodiment, an equal mass of lithium fluoride is used to replace manganese fluoride.
[0092] The sodium ion battery positive electrode material S3 is prepared.
[0093] Example 4
[0094] This embodiment prepares a sodium ion battery positive electrode material, and its preparation method is basically the same as the preparation method of Example 1, except that in step (3) of this embodiment, an equal mass of cobalt fluoride is used to replace manganese fluoride.
[0095] The sodium ion battery positive electrode material S4 is prepared.
[0096] Example 5
[0097] (1) Preparation of the matrix: Sodium carbonate, nickel oxide, manganese carbonate and titanium dioxide were fully ground in a molar ratio of 1.03:0.50:0.35:0.15 in an agate mortar and subjected to a second sintering in the presence of air to obtain a matrix Na 1.0 Ni 0.50 Mn 0.35 Ti 0.15 O2; the second sintering conditions are: heating rate of 1 ° C / min, temperature of 960 ° C, time of 15h;
[0098] (2) Preparation of positive electrode material for sodium ion battery: In the presence of air atmosphere, 100 g of the substrate obtained in step (1), 0.8 g of manganese tetraoxide, and 0.2 g of manganese fluoride are mixed and subjected to a first sintering to obtain the positive electrode material S5 for sodium ion battery; the conditions of the first sintering are: temperature of 550° C., time of 6 h, and heating rate of 2° C. / min.
[0099] Example 6
[0100] This embodiment prepares a sodium ion battery positive electrode material, and the specific preparation steps are as follows:
[0101] (1) Preparation of precursor (metal M-containing hydroxide): nickel sulfate, iron sulfate and manganese sulfate were dissolved in 1000 mL of water at a molar ratio of Ni:Fe:Mn of 0.33:0.33:0.33 to obtain a mixed solution with a metal ion concentration of 1 mol / L, and then 50 mL of 20 wt% ammonia water and 80 mL of 38 wt% sodium hydroxide solution were added to perform precipitation reaction. After solid-liquid separation of the obtained reaction product, the solid product was washed and dried in turn to obtain a precursor Ni with a D50 of 3.5 μm. 0.33 Fe 0.33 Mn 0.33 (OH)2; the conditions of the precipitation reaction are: temperature 70°C, time 55h;
[0102] (2) Preparation of substrate: In the presence of air, the precursor obtained in step (1) was mixed with Na2CO3 at a molar ratio of n(Na) / n(M) of 1.03, and then subjected to a second sintering to obtain a substrate Na 1.0 Ni 0.33 Fe 0.33 Mn 0.33 O2; the second sintering conditions are: heating rate of 1 ° C / min, temperature of 960 ° C, time of 15h;
[0103] (3) Preparation of positive electrode material for sodium ion battery: In the presence of air atmosphere, 100 g of the substrate obtained in step (2), 0.8 g of manganese tetraoxide, and 0.2 g of manganese fluoride are mixed and sintered for the first time to obtain the positive electrode material S6 for sodium ion battery; the conditions of the first sintering are: temperature of 550°C, time of 6h, and heating rate of 2°C / min.
[0104] Example 7
[0105] In this embodiment, a sodium ion battery positive electrode material is prepared. The preparation method is basically the same as the preparation method in Example 1, except that in step (3) of this embodiment, the amount of manganese tetraoxide is 4 g and the amount of manganese fluoride is 1 g.
[0106] The sodium ion battery positive electrode material S7 was prepared.
[0107] Example 8
[0108] In this embodiment, a sodium ion battery positive electrode material is prepared. The preparation method thereof is substantially the same as the preparation method of Embodiment 1, except that, in this embodiment, the temperature of the first sintering is 700° C.
[0109] The sodium ion positive electrode material S8 is prepared.
[0110] Control group
[0111] In the control group, manganese tetraoxide, manganese fluoride and sodium carbonate were mixed in the presence of air atmosphere and sintered. The sintering conditions were: temperature of 550°C, time of 6h, heating rate of 2°C / min, and fluorine-doped sodium manganate was obtained. Figure 6 This is the XRD pattern of the fluorine-doped sodium manganate prepared in this control group.
[0112] Comparative Example 1
[0113] In this comparative example, a sodium ion battery positive electrode material is prepared. The preparation method is basically the same as the preparation method in Example 1, except that in step (3), 1 g of P2 phase Na 0.66 Cu 0.35 Mn 0.65 O 1.98 F 0.02 In Example 1, 0.8 g of trimanganese tetraoxide and 0.2 g of manganese fluoride were substituted.
[0114] The material DS1 was prepared.
[0115] Comparative Example 2
[0116] In this comparative example, a sodium ion battery positive electrode material is prepared. The preparation method is basically the same as the preparation method in Example 1, except that in step (3), 1 g of aluminum oxide is used to replace 0.8 g of manganese tetraoxide and 0.2 g of manganese fluoride in Example 1.
[0117] The material DS2 was prepared.
[0118] Comparative Example 3
[0119] In this comparative example, a sodium ion battery positive electrode material is prepared. The preparation method is basically the same as the preparation method in Example 1, except that in step (3), 1 g of O3 phase Na 0.98 Cu 0.5 Mn 0.5 O 1.98 F 0.02 In Example 1, 0.8 g of trimanganese tetraoxide and 0.2 g of manganese fluoride were substituted.
[0120] Material DS3 was prepared.
[0121] Comparative Example 4
[0122] This comparative example uses the substrate prepared in Example 1 as the positive electrode material DS4 for comparison.
[0123] Comparative Example 5
[0124] This comparative example uses the substrate prepared in Example 5 as the positive electrode material DS5 for comparison.
[0125] Comparative Example 6
[0126] This comparative example uses the substrate prepared in Example 6 as the positive electrode material DS6 for comparison.
[0127] The positive electrode materials prepared in the above examples and comparative examples were tested, specifically:
[0128] 1. The particle size (D50) is tested by Malvern 3000 laser particle size analyzer, with reference to GB / T19077-2016;
[0129] 2. XRD was measured by X-ray diffractometer, and the crystal structure of each sample was tested by Rigaku SmartLab 9kW X-ray diffractometer (XRD, Cu Kα) with a scanning range of 5-80° and a scanning rate of 8° / min;
[0130] 3. The coating thickness is measured by the cross-sectional electron microscope image of the positive electrode material: select 5 positions along the edge of the positive electrode material particle cross section, measure the coating thickness corresponding to the 5 positions, and calculate the average thickness as the coating thickness.
[0131] The specific results are shown in Table 1.
[0132] Table 1
[0133]
[0134] Test Example 1
[0135] The pH value and residual sodium content of the positive electrode materials obtained in the above examples and comparative examples were tested, and the test method was as follows:
[0136] (1) pH value test: 5 g of sample and 45 g of deionized water were placed in a 50 mL conical flask and magnetically stirred for 10 min before pH test. The pH electrode liquid level was between 1 / 3 and 2 / 3 and the test solution temperature was 25 ± 1 °C.
[0137] (2) Residual sodium test: Take 10 g of sample and 90 g of deionized water, place them in a magnetic stirrer and stir for 10 min, then filter with a vacuum circulating water pump; take the supernatant and test it with a potentiometric titrator, and calculate the residual sodium content based on the volume values corresponding to the two isoelectric points on the titration curve of the potentiometric titrator.
[0138] The test results are shown in Table 2.
[0139] Table 2
[0140] pH <![CDATA[Na + (wt%)]]> Example 1 12.18 0.324 Example 2 12.11 0.285 Example 3 12.15 0.338 Example 4 12.17 0.365 Example 5 12.17 0.318 Example 6 12.19 0.336 Example 7 12.05 0.241 Example 8 12.18 0.342 Comparative Example 1 12.20 0.552 Comparative Example 2 12.01 0.338 Comparative Example 3 12.17 0.533 Comparative Example 4 12.22 0.502 Comparative Example 5 12.35 0.491 Comparative Example 6 12.31 0.527
[0141] It can be seen from the results in Table 2 that the sodium ion battery positive electrode material obtained in the present invention has a lower residual sodium content than the substrate surface without the coating layer.
[0142] Test Example 2
[0143] The electrochemical properties of the positive electrode materials obtained in the above examples and comparative examples were tested, and the test method was as follows:
[0144] (1) Preparation of positive electrode sheets: Weigh the positive electrode material, conductive agent (Super P), and binder (polyvinylidene fluoride PVDF) in a mass ratio of 85:10:5 and place them in a weighing bottle, add an appropriate amount of dispersing solvent (N-methylpyrrolidone NMP), stir evenly, and then coat them on aluminum foil, followed by drying, rolling, and slicing to produce the required positive electrode sheets.
[0145] (2) Assembly and testing of sodium ion batteries: All batteries used CR2032 button batteries. The batteries were assembled in the order of positive electrode shell, gasket, positive electrode sheet prepared in step (1), separator, electrolyte, sodium metal negative electrode, gasket, spring, and negative electrode shell. They were then placed in a button battery sealing machine for packaging. After being removed and left to stand for a period of time, the electrochemical performance was tested on a blue battery test system. The voltage range was set to 2.0-4.3V, the test rate was 0.1C (1C = 150mAh / g), activated for 2 cycles, then activated for 2 cycles at 0.2C, and finally cycled for 50 cycles at 1C. The test temperature was 25±1°C.
[0146] The test results are shown in Table 3.
[0147] Table 3
[0148] 1C first discharge capacity mAh / g <![CDATA[1C-50 th Capacity retention rate %]]> Example 1 157.00 97.03 Example 2 153.23 97.28 Example 3 156.71 96.48 Example 4 156.69 96.36 Example 5 148.77 88.25 Example 6 150.60 90.49 Example 7 152.87 97.48 Example 8 152.02 97.54 Comparative Example 1 150.01 93.24 Comparative Example 2 156.58 92.01 Comparative Example 3 154.89 91.88 Comparative Example 4 157.95 91.29 Comparative Example 5 149.35 84.80 Comparative Example 6 151.53 84.11
[0149] It can be seen from the results in Table 3 that the sodium ion battery positive electrode material having the coating layer provided by the present invention has better comprehensive electrochemical performance when applied to button batteries.
[0150] Figure 1 The discharge specific capacity of the battery assembled with the positive electrode materials obtained in Comparative Examples 1-3 and Example 1 at 0.1C, 0.2C, and 1C rates in the voltage range of 2.0-4.3V. It can also be seen from the figure that the discharge specific capacity of the battery assembled with the positive electrode material obtained in Example 1 at 1C rate decreases more slowly, and the cycle stability is better;
[0151] Figure 2 The batteries assembled with the positive electrode materials obtained in Example 1 and Comparative Example 4 have a discharge medium voltage in the voltage range of 2.0-4.3V at rates of 0.1C, 0.2C, and 1C. It can be seen from the figure that compared with Comparative Example 4, the decreasing trend of the discharge medium voltage in Example 1 is slower.
[0152] Test Example 3
[0153] Figure 3 This is a SEM image of the sodium ion battery positive electrode material obtained in Example 1 of the present invention. Figure 3 It can be seen that the positive electrode material is a single crystal with a relatively smooth surface, indicating that the P2 phase coating layer is evenly distributed, which is beneficial to isolate the contact between the substrate and the electrolyte and reduce the dissolution of transition metal ions.
[0154] Figure 4 The XRD spectrum of the sodium ion battery positive electrode material obtained in embodiment 1 of the present invention is as follows: Figure 4 It can be seen that the positive electrode material is a mixed phase of P2 and O3. In order to further verify that the coating layer of the positive electrode material of the sodium ion battery obtained by the present invention has a P2 phase structure, the present invention uses fluorine-doped sodium manganate generated by the reaction of manganese tetraoxide, manganese fluoride and sodium carbonate as a control. Figure 5 The XRD pattern of sodium fluoride manganate obtained for the control group is Figure 5 It can be seen that it is fluorine-doped sodium manganate of the P2 phase.
[0155] Figure 6 This is a cross-sectional EPMA image of the sodium ion battery positive electrode material obtained in Example 1. Figure 6 It can be seen that a large amount of fluorine elements are gathered at the edge of the material; the stronger Mn-F bond can not only reduce the dissolution of manganese elements caused by hydrogen fluoride corrosion, but also alleviate the 3+ Lattice distortion caused by the Jan-Taylor effect.
[0156] Figure 7 This is a cross-sectional view of the sodium ion positive electrode material provided in Example 1 of the present invention. Five positions are selected at random from the edge of the cross section, and the thickness of the coating layer corresponding to the five positions is measured. The average thickness is calculated to be 12 nm. Figure 8 This is a diagram of selected fluorine element analysis points of the cross-section EDS of the positive electrode material obtained in Example 1 provided by the present invention. The test results are shown in Table 4.
[0157] Table 4
[0158]
[0159] It can be seen from the table that the fluorine element concentration contained in the single crystal particle matrix of the positive electrode material obtained by the present invention is lower than the fluorine element concentration contained in the coating layer, wherein Weight% represents the element weight percentage, and Atomic% represents the atomic percentage. From the data, the fluorine element weight percentage and atomic percentage at site 3 and site 4 are both lower than the fluorine element weight percentage and atomic percentage at site 1 and site 2.
[0160] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A sodium ion battery positive electrode material, characterized in that: The positive electrode material includes a matrix and a coating layer coated on the surface of the matrix, the matrix includes a layered oxide; the coating layer includes Na x Mn 1-y M' y O z F β , where 0.6 < x < 0.8, 0 < y ≤ 0.05, 1.9 < z ≤ 2.1, 0 < β ≤ 0.05, and M' is selected from at least one of Ni, Fe, Co, Ti, Li, and Mn.
2. The sodium ion battery positive electrode material according to claim 1, characterized in that The matrix includes a layered oxide having an O3 phase; Optionally, the chemical general formula of the layered oxide is Na i MF α O j , where 0.6 < i < 1.1, 0 ≤ α ≤ 0.05, 1.9 < j ≤ 2.1, and M is selected from at least one of Ni, Fe, Mn, Co, Ti, Cu, Ca, Zn, Mg, Al, Y, Ce, Sr, Sn, Ba, La, and Li.
3. The sodium ion battery positive electrode material according to claim 2, characterized in that The mass ratio of the P2 phase to the O3 phase is (0.01-0.05):
1.
4. The sodium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that The positive electrode material satisfies at least one of the following conditions: a. The concentration of fluorine contained in the substrate is less than the concentration of fluorine contained in the coating layer; b. The chemical general formula of the coating layer is Na x Mn 1-y M' y O z F β , where 0.6 < x < 0.7, 0 < y ≤ 0.02, 1.9 < z ≤ 2.1, 0 < β ≤ 0.02, and M' is selected from at least one of Mn, Co, and Li; c. The average thickness of the coating layer is 5-50nm; d. The D50 of the positive electrode material is 3-20 μm; e. The mass of the coating layer accounts for 1-5% of the mass of the substrate.
5. A method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 4, characterized in that: The method comprises: The positive electrode material is obtained by first sintering a first mixture including a manganese-containing compound, a fluoride containing M' and the matrix.
6. The method according to claim 5, characterized in that The method satisfies at least one of the following conditions: (1) The manganese-containing compound is selected from at least one of MnCO3, MnO, Mn2O3, MnO2, Mn2O7, and Mn3O4; (2) the M' in the M'-containing fluoride is selected from at least one of Ni, Fe, Co, Ti, Li, and Mn; (3) The first sintering temperature is 400-700° C., and the time is 4-8 hours; optionally, the first sintering temperature is 500-600° C., and the time is 6-8 hours; (4) The heating rate of the first sintering is 1-5°C / min; optionally, the heating rate of the first sintering is 1-3°C / min; (5) The matrix is a polycrystalline particle or a single crystal particle; (6) The mass ratio of the coating layer to the substrate in the first mixture is (0.01-0.05):
1.
7. The method for preparing a positive electrode material for a sodium ion battery according to claim 5, characterized in that: The matrix is obtained by performing a second sintering on a second mixture including a sodium source and a metal M source.
8. The method for preparing a positive electrode material for a sodium ion battery according to claim 7, characterized in that: The method satisfies at least one of the following conditions: A. the sodium source is selected from at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate; B. the metal M source is selected from at least one of an oxide containing metal M, a hydroxide containing metal M, and a carbonate containing metal M; C. M in the metal M source is selected from at least one of Ni, Fe, Mn, Co, Ti, Cu, Ca, Zn, Mg, Al, Y, Ce, Sr, Sn, Ba, La, and Li; D. The second sintering temperature is 800-1100°C and the time is 10-15h; E. The heating rate of the second sintering is 1-3°C / min; F. The element molar ratio of sodium to metal M in the second mixture is (0.6-1.1):
1.
9. A sodium ion battery, characterized in that: The invention comprises the sodium ion battery positive electrode material according to any one of claims 1 to 4.
10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.
Citation Information
Patent Citations
Compounding and coating method of anode material for lithium ion cell
CN103022502A
Lithium ion secondary battery and method for manufacturing same
CN103959543A
Core-shell structure sodium ion battery positive electrode material and preparation method and application thereof
CN110277540A
Fluoride / oxide co-coated positive electrode material and preparation method thereof
CN112151798A
Composite positive electrode material and preparation method thereof
CN113991079A
Cited By
Coated modified sodium ion positive electrode material and preparation method and application thereof
CN121215726A